Interview with Micha Espinosa and Garrett Johnson - Ybarra, Patricia (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2020)
In this interview with Fitzmaurice Voicework practitioner and La Pocha Nostra performer Micha Espinosa and her collaborator Garrett Johnson, Patricia Ybarra and her interlocutors ask: "How do we fight through sound against the state under fascism and racial capitalism?"